The role of teriparatide in sequential and combination therapy of osteoporosis (Swiss Medical Weekly, 2014)
Osteoporosis is complicated by the occurrence of fragility fractures. Over past years, various treatment options have become available, mostly potent antiresorptive agents such as bisphosphonates and denosumab. However, antiresorptive therapy cannot fully and rapidly restore bone mass and structure that has been lost because of increased remodelling. Alternatively recombinant human parathyroid hormone (rhPTH) analogues do increase the formation of new bone material. The bone formation stimulated by intermittent PTH analogues not only increases bone mineral density (BMD) and bone mass but also improves the microarchitecture of the skeleton, thereby reducing incidence of vertebral and nonvertebral fractures. Teriparatide, a recombinant human PTH fragment available in Switzerland, is reimbursed as second-line treatment in postmenopausal women and men with increased fracture risk, specifically in patients with incident fractures under antiresorptive therapy or patients with glucocorticoid-induced osteoporosis and intolerance to antiresorptives. This position paper focuses on practical aspects in the management of patients on teriparatide treatment. Potential first-line indications for osteoanabolic treatment as well as the benefits and limitations of sequential and combination therapy with antiresorptive drugs are discussed.